Connecting Vietnam's silicone valley to enhance high quality science and technology human resources for innovation-based entrepreneurs - Dung, Nguyen Thi Ngoc (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
The government has issued policies to attract Vietnamese talents from all over the world to return home to conduct scientific research, technology development and innovation. Silicon Valley is a world-renowned destination for technology innovation and innovation based entrepreneurship, where it attracts the most talent from around the globe to work and start successful businesses, creating a perfect ecosystem to incubate technology talents, including the Vietnamese community who have succeeded and accumulated full resources. In recent years, the Vietnamese community working in the fields of scientific research, technology development and innovation has tended to move to Vietnam to start a business based on innovation. The culture of Silicon Valley has influenced them and helped them succeed. This article provides answers to the question: (i) What factors have caused this social mobility of talents; (ii) Why do they come back to Vietnam to start a business; and (iii) What should the government continue to do to retain and promote people who are passionate about science and technology to transform their carriers from being researcher to technological entrepreneur, thereby creating future technological entrepreneurs, driving economic growth domestically and have international influence. Code: 21050701